Kynurenic Acid: The Janus-Faced Role of an Immunomodulatory Tryptophan Metabolite and Its Link to Pathological Conditions - Wirthgen, Elisa; Hoeflich, Andreas; Rebl, Alexander; Günther, Juliane (Frontiers in Immunology, 2018)
Tryptophan metabolites are known to participate in the regulation of many cells of the immune system and are involved in various immune-mediated diseases and disorders. Kynurenic acid (KYNA) is a product of one branch of the kynurenine pathway of tryptophan metabolism. The influence of KYNA on important neurophysiological and neuropathological processes has been comprehensively documented. In recent years, the link of KYNA to the immune system, inflammation, and cancer has become more apparent. Given this connection, the anti-inflammatory and immunosuppressive functions of KYNA are of particular interest. These characteristics might allow KYNA to act as a “double-edged sword”. The metabolite contributes to both the resolution of inflammation and the establishment of an immunosuppressive environment, which, for instance, allows for tumor immune escape. Our review provides a comprehensive update of the significant biological functions of KYNA and focuses on its immunomodulatory properties by signaling via G protein-coupled receptor 35 (GPR35)- and aryl hydrocarbon receptor-mediated pathways. Furthermore, we discuss the role of KYNA-GPR35 interaction and microbiota associated KYNA metabolism for gut homeostasis.